2013
DOI: 10.11604/pamj.2013.14.72.2131
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic immunoassays for Helicobacter pylori detection - are they reliable in Mali, West Africa?

Abstract: IntroductionGastrointestinal diseases are major reasons for morbidity in Mali. As Helicobacter pylori is known to play a major role in gastritis and gastric ulcer we wanted to find a simple method for detection.MethodsTwenty-nine volunteers with confirmed gastric ulcer by gastroscopy and 59 randomly selected volunteers were diagnosed by using the rapid serological test Clearview® H. Pylori. The ImmunoCard STAT!® HpSA®test was applied on stool from 65 volunteers seeking help for gastrointestinal related ailment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Surprisingly, an unusually low prevalence has been demonstrated in Mali where a rate of 21% was reported among persons with established gastric ulcer, 44% among the casually selected volunteers and 14% in those with gastrointestinal correlated illnesses. This low prevalence in the study population was attributed to the sensitivity of the detection kit [63] due to a possible H. pylori strain variability. Generally, the disease prevalence across countries in the West African area varies and there is no clear show of a steady overall increment or decrease with age.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, an unusually low prevalence has been demonstrated in Mali where a rate of 21% was reported among persons with established gastric ulcer, 44% among the casually selected volunteers and 14% in those with gastrointestinal correlated illnesses. This low prevalence in the study population was attributed to the sensitivity of the detection kit [63] due to a possible H. pylori strain variability. Generally, the disease prevalence across countries in the West African area varies and there is no clear show of a steady overall increment or decrease with age.…”
Section: Resultsmentioning
confidence: 99%
“…In that report, Austarheim et al. found a sensitivity of 21% only for H. pylori stool antigen test in Mali in patients with gastric ulcer, although previous studies had reported 95% prevalence of H. pylori infection in Mali [21]. This lack of an appropriate gold standard for the diagnosis of H. pylori in Mali is therefore a limitation of this study.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to this, it has been recently reported that the stool antigen test is a poor diagnostic test for the detection of H. pylori in Mali, which was not known when this study was conducted. In that report, Austarheim et al found a sensitivity of 21% only for H. pylori stool antigen test in Mali in patients with gastric ulcer, although previous studies had reported 95% prevalence of H. pylori infection in Mali[21]. This lack of an appropriate gold standard for the diagnosis of H. pylori in Mali is therefore limitation of this study.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…As opposed to Asian countries that have a very high GC incidence, African countries have less subjects that develop GC. This phenomenon is called the "African enigma" [8][9][10][11][12]. In addition, the prevalence of infection and GC is affected by factors like age, environment, ethnicity, region of origin, smoking, alcohol consumption, immune status, diet, and the performance of diagnostic methods [13][14][15].…”
Section: Introductionmentioning
confidence: 99%